2009
DOI: 10.1021/jp908548f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Cobalt Hydroxide, Cobalt Oxyhydroxide, and Cobalt Oxide Nanodiscs

Abstract: Cobalt hydroxide, cobalt oxyhydroxide, and cobalt oxide nanomaterials were synthesized through simple soft chemistry. The cobalt hydroxide displays hexagonal morphology with clear edges 20 nm long. This morphology and nanosize is retained through to cobalt oxide Co3O4 through a topotactical relationship. Cobalt oxyhydroxide and cobalt oxide nanomaterials were synthesized through oxidation and low-temperature calcination from the as-prepared cobalt hydroxide. Characterization of these cobalt-based nanomaterials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

151
1,044
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,398 publications
(1,199 citation statements)
references
References 50 publications
151
1,044
0
4
Order By: Relevance
“…14,20 They tend to produce large ca. 500 nm aggregates of clustered 20 nm × 20 nm hexagonal nanocrystals, although certain conditions yield isolated 120 nm × 120 nm hexagonal nanocrystals.…”
Section: −23mentioning
confidence: 99%
See 1 more Smart Citation
“…14,20 They tend to produce large ca. 500 nm aggregates of clustered 20 nm × 20 nm hexagonal nanocrystals, although certain conditions yield isolated 120 nm × 120 nm hexagonal nanocrystals.…”
Section: −23mentioning
confidence: 99%
“…250 nm amorphous flake-like regions (Table 1, Figure 5). 14 The crystalline domain (grain size) obtained from XRD peak Figure 6). This implies that neither hexaaquacobalt(III) nor hexaaquacobalt(II) is a competent intermediate in forming Co(O)OH.…”
Section: −28mentioning
confidence: 99%
“…8) Further, it is reported that nano ower-shaped Co 3 O 4 particles show highly reversible lithium storage capability by Chen et al The nano ower was synthesized by way of thermal treatment of the ower-shaped precursor obtained by a solvothermal method. 21) Co 3 O 4 nanocubes, [29][30][31] nanosheets, [32][33][34] nanorings, 35) nanowires, 8,36) nanospheres, 37) and nanoparticles [38][39][40] 43) However, all the approaches have been carried out at low concentrations so that to prevent the aggregation between the particles among the growth process (0.001 0.1 mol/L). For the practical usage of Co 3 O 4 -based nanomaterials, development of a liquid-phase direct synthetic process of Co 3 O 4 nanoparticles under a highly concentrated condition to obtain the desired particles in large quantity.…”
Section: Introductionmentioning
confidence: 99%
“…Um dos materiais modificadores, que pode ser capaz de auxiliar a eletrooxidação de tramadol é o oxihidróxido de cobalto trivalente CoO(OH), um semicondutor do tipo p, visto por alguns pesquisadores [36][37][38][39][40] como alternativa ao dióxido de titânio nos sistemas de foto e fotoeletrocatálise. O estudo das suas propriedades eletroanalíticas começou recentemente [41,42], mas já foi mostrado, experimental e teoricamente [43][44][45][46], que o CoO(OH) pode ser ótimo mediador de oxidação de compostos orgânicos em meios neutro e levemente alcalino.…”
Section: Introductionunclassified